Physical education and sports students' education quality satisfaction level - Bahadir Kayısoglu; Yilmaz Yuksel (Selcuk University, 2016)
The purpose of this descriptive study carried out through survey method was to determine the satisfaction levels of the students of Hasan Doğan School of Physical Education and Sports at Karabük University with regard to educational services provided by the department. The study focused on the factors like age, gender, department and grade level. The study group of the research, consisting of 361 students, was chosen randomly from the students who attended the department of Physical Education and Sport Teaching and Sports Management in the academic year of 2014-2015. The data of the study were collected through an adapted 5-point likert questionnaire. Cronbach's alpha of the questionnaire was .94. Results indicated that student's satisfaction level in physical condition of the department is high but the level of efficiency of course and lecturers is moderate.